2017
DOI: 10.14254/2071-789x.2017/10-3/10
|View full text |Cite
|
Sign up to set email alerts
|

Students' Career Preferences: Intercultural Study of Croatian and German Students

Abstract: ABSTRACT. Students' career preferences are an important issue to various stakeholders: to university administration, career counselors, higher education policy makers as well as to human resource managers in companies. Students, whose career preferences and goals are fulfilled, are better and more highly motivated employees. By a questionnaire survey carried out in 2016 in two institutions of higher education the present study compares career preferences and attitudes of 478 German and Croatian students. Facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 30 publications
5
28
0
Order By: Relevance
“…Job security was reported as influential in only one study where it was identified as highly important by German youth in comparison to their Croatian counterparts (Wüst and Leko Šimić, 2017). They suggested that their finding are in line with the uncertainty avoidance index proposed by Hofstede (2011) which also takes on a relatively high value for Germans.…”
Section: Job Securitymentioning
confidence: 85%
See 4 more Smart Citations
“…Job security was reported as influential in only one study where it was identified as highly important by German youth in comparison to their Croatian counterparts (Wüst and Leko Šimić, 2017). They suggested that their finding are in line with the uncertainty avoidance index proposed by Hofstede (2011) which also takes on a relatively high value for Germans.…”
Section: Job Securitymentioning
confidence: 85%
“…No articles focused solely on extrinsic or intrinsic factors. Two studies each explored the relationship between intrinsic and extrinsic (Choi and Kim, 2013;Atitsogbe et al, 2018) as well as extrinsic and interpersonal factors (Yamashita et al, 1999;Wüst and Leko Šimić, 2017). The remaining five articles (17%) explored all three factors (intrinsic, extrinsic, and interpersonal, (Bojuwoye and Mbanjwa, 2006;Agarwala, 2008;Gokuladas, 2010;Fan et al, 2012;Tao et al, 2018).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations